Reply to the comments on: From source-to-sink: The Late Permian SW gondwana paleogeography and sedimentary dispersion unraveled by a multi-proxy analysis [journal of South American earth sciences 70 (2016) 368-382] by Vesely & Schemiko - Alessandretti, Luciano (2017)
The publication of the comments by Vesely & Schemiko (Comment on From source-to-sink: The Late Permian SW Gondwana paleogeography and sedimentary dispersion unraveled by a multi-proxy analysis by L. Alessandretti, R. Machado, L.V. Warren, M.L. Assine and C. Lana [Journal of South American Earth Sciences 70 (2016) 368-382], Journal of South American Earth Sciences, this issue) on our paper entitled From source-to-sink: The Late Permian SW Gondwana paleogeography and sedimentary dispersion unraveled by a multi -proxy analysis (L. Alessandretti, R. Machado, L.V. Warren, M.L. Assine and C. Lana (Journal of South American Earth Sciences 70 (2016) 368-382) provides a worthy opportunity to further clarify our observations and interpretations regarding the provenance of the Late Permian Rio do Rasto Formation and its implications on SW Gondwana paleogeography and sedimentary dispersion. (C) 2017 Elsevier Ltd. All rights reserved.